Large inter-rater variability on EEG-reactivity is improved by a novel quantitative method. Issue 4 (April 2018) - Duez, Christophe Henri Valdemar; Ebbesen, Mads Qvist; Benedek, Krisztina; Fabricius, Martin; Atkins, Mary Doreen; Beniczky, Sandor; Kjaer, Troels W.; Kirkegaard, Hans; Johnsen, Birger
Highlights: There is a large inter-rater variation among experts in the evaluation of EEG-reactivity. Quantitative measurement of EEG-reactivity is a promising prognostic parameter. Traditional qualitative evaluation of EEG-Reactivity should be interpreted with caution. Abstract: Objective: To assess inter-rater agreement on EEG-reactivity (EEG-R) in comatose patients and compare it with a quantitative method (QEEG-R). Methods: Six 30-s stimulation epochs (noxious, visual and auditory) were performed during EEG on 19 neurosurgical and 11 cardiac arrest patients. Six experts analysed EEGs for reactivity using their habitual methods. QEEG-R was defined as present if ≥2/6 epochs were reactive (stimulation/rest power ratio exceeding noise level). Three-months patient outcome was assessed by the Cerebral Performance Category Score (CPC) dichotomized in good (1–2) or poor (3–5). Results: Agreement among experts on overall EEG-R varied from 53% to 83% ( κ : 0.05–0.64) and reached 100% ( κ : 1) between two QEEG-R calculators. For the experts, absence of EEG-R yielded sensitivities for poor outcome between 40–85% and specificities between 20–90%, for QEEG-R sensitivity was 40% (CI: 23–68%) and specificity 100% (CI: 69–100%). Conclusions: There is a large inter-rater variation among experts on EEG-R assessment in comatose patients. QEEG-R is a promising objective prognostic parameter with low inter-rater variation and a high specificity for prediction of poor outcome. Significance: Clinicians should be cautious when using the traditional, qualitative method, in particular in end-of-life decisions. Implementation of the quantitative method in clinical practice may improve reliability of reactivity assessments.